Pendidikan Islam dan Dinamika Sosial: Studi Komparatif Masa Demokrasi Parlementer dan Era Digital - Ana dwi Lestari; Anggi Anggraini; Triyo Supriyatno (Peradaban Journal of Interdisciplinary Educational Research, 2025)
This study analyzes the dynamics of Islamic education in Indonesia through a historical-comparative approach between the Parliamentary Democracy period (1950–1959) and the contemporary digital era. The primary goal is to map the patterns of continuity and change in how Islamic education responded to distinct social-political and technological challenges. Using a qualitative methodology based on literature review, the article finds that the struggles of Islamic education during the Parliamentary Democracy era were centered on political and institutional legitimacy within the newly emerging national system. In contrast, challenges in the digital era have shifted to the realm of functional adaptation and the negotiation of authority amid technological disruption. This finding confirms that Islamic education is not a static entity but a dynamic social agent with high adaptive capacity. Theoretically, this study enriches the literature on the social history of Islamic education by providing a comparative analytical framework. Practically, it underscores the urgency of curriculum renewal, strengthening digital literacy, and fostering collaboration among stakeholders to ensure the ongoing relevance of Islamic education. Penelitian ini menganalisis dinamika pendidikan Islam di Indonesia melalui pendekatan historis-komparatif antara periode Demokrasi Parlementer (1950-1959) dan era digital kontemporer. Tujuan utamanya adalah untuk memetakan pola kontinuitas dan perubahan pendidikan Islam dalam merespons tantangan sosial-politik dan teknologi yang berbeda. Menggunakan metodologi kualitatif berbasis kajian literatur, artikel ini menemukan bahwa perjuangan pendidikan Islam pada masa Demokrasi Parlementer berpusat pada legitimasi politik dan institusional dalam sistem nasional yang baru. Sebaliknya, tantangan di era digital bergeser ke ranah adaptasi fungsional dan negosiasi otoritas di tengah disrupsi teknologi. Temuan ini menegaskan bahwa pendidikan Islam bukanlah entitas statis, melainkan agen sosial yang dinamis dengan kapasitas adaptif yang tinggi. Secara teoretis, kajian ini memperkaya literatur sejarah sosial pendidikan Islam dengan menghadirkan kerangka analitis komparatif. Secara praktis, ia menggarisbawahi urgensi pembaruan kurikulum, penguatan literasi digital, dan kolaborasi antar-aktor untuk menjaga relevansi pendidikan Islam di masa kini.